Recreación morfológica de los motivos de cerámica precolombina mediante el relevamiento fotógrafico de las colecciones disponibles en la ciudad de Latacunga provincia de Cotopaxi, aplicado a la identidad visual del proyecto Panzaleo - LLumiquinga Chicaiza, Walter Fabián (2017)
The present project is a participative investigation witch illustrates the importance of valuing the visual and iconographic richness of the ancestral towns of Ecuador, and its relation to the project “Inclusion of pre-Hispanic cultures of the Panzaleo Town in the modern graphic design,” at the Technical University of Cotopaxi. Pre-Colombian ceramic items, witch allwed the researches to analyze and to understand the formal and structural elements of archeological pieces, by different constructive techniques such as geometry to stylish and to clean traces, morphological squares were also used for the formal elaboration of new iconographic motives; plus this antecedent, it was possible to register in the project inventory a collection of twenty archeological pieces that belongs to the Panzaleo Culture found in the San Juan Bautista Manufacturing Farm in the Tilipulo-Latacunga. Likewise, there was a deep thought of the benefit that brings the photographic development as a technique of anthropological registration....